Python programming a practical approach - Śarmā, Vijaya Kumāra; Kumar, Vimal; Sharma, Swati; Pathak, Shashwat (Boca Raton, FL CRC Press, an imprint of the Taylor & Francis Group, 2022)
"Purposefully designed to be instantly applicable, PYTHON PROGRAMMING - A PRACTICAL APPROACH provides implementation examples so that the described subject matter can be immediately implemented, and reader will try to implement same in the practical problems due to well-known versatility of Python in handling different data types with ease"--Provided by publisher.
"A Chapman & Hall book"
Includes bibliographical references and index.
Keywords: Python (Computer program language); Computer programming